Propuesta de línea base del plan de ordenamiento forestal para la Estación Experimental Forestal Horizontes, Área de Conservación Guanacaste, Costa Rica. - Rigg-Aguilar, Priscilla (Instituto Tecnológico de Costa Rica, 2013)
An extensive review of literature itself and external of the Estación Experimental Forestal Horizontes, Área de Conservación Guanacaste, Costa Rica, was conducted to determine their present state in an overall level of management activities, projects and programs monitoring, and the state of natural resources (soil, water mains, natural forests and forest plantations) and the status of priority roads. The present state of the forest and non-forest cover was performed by field visits and their characterization for subsequent zoning. It was determined that the predominant coverage is secondary forest in different stages (5053,83 ha), followed by wooded pastures (1826,14 ha), shrub lands (250,98 ha), grassland (124,4 ha) and forest plantations (95,67 ha). With each sector categorized, variables analysis was performed to identify the management sectors, considering accessibility, soil capacity use, usability and production potential. It was determined that there 1028,85 ha of secondary forests with basal area higher than 12 m2/ha, with potential use in the next 5 years , 35 ha of mixed plantations of native species with characteristics of short-term use, as well as 951,44 ha of pasture woodlands, grasslands and shrub lands propitious to establishment of forest plantations. The roads have drainage problems and flooding, caused by vertic soil characteristics, which do not have optimal drainage conditions and the absence of a proper drainage system water (ditches, culverts). In total of 39,4 km of roads, 10,05% were classified with category 1, a 58,72% to category 2 , and 31,22% category 3, where 1 is the best condition and 3 the worst condition.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2013.
Keywords: Ordenación forestal; Bosque; Plantaciones; Manejo de plantaciones; Manejo sostenible